GE_GERICHTE C/13902/2012 vom 19. Juni 2015 - GE Cour de justice (2015)
DIVORCE; VISITE; OBLIGATION D'ENTRETIEN; MESURE PROVISIONNELLE; AVANCE DE FRAIS; CONJOINT | CC.273.1; CC.176.3; CC.125; CPC.276.3